Autocracy and resistance in the internet age - Vanderhill, Rachel (Boulder, Colorado : Lynne Rienner Publishers, Inc., 2020)
"Explores in detail how social media are both aiding and undermining autocratic regimes in the Middle East, North Africa, and the former Soviet republics"--
The revolution will be Tweeted ... or not? -- Authoritarian regimes and information communication technology -- Censorship, surveillance, and propaganda : the cases of Iran and Russia -- Protest without change : the cases of Armenia and Moldova -- Regime overthrow is not democratization : the cases of Kyrgyzstan and Egypt -- From protest to democratization : the case of Tunisia -- Autocracy in the internet age.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on August 06, 2020).
eBooks on EBSCOhost
Keywords: Authoritarianism -- Former Soviet republics; Authoritarianism -- Russia (Federation); Authoritarianism -- Middle East; Internet -- Political aspects -- Former Soviet republics; Internet -- Political aspects -- Russia (Federation); Internet -- Political aspects -- Middle East; Social media -- Political aspects -- Former Soviet republics; Social media -- Political aspects -- Russia (Federation); Social media -- Political aspects -- Middle East; Autoritarisme -- Ex-URSS.; Autoritarisme -- Russie; Internet -- Aspect politique -- Ex-URSS.; Internet -- Aspect politique -- Russie; Médias sociaux -- Aspect politique -- Ex-URSS.; Médias sociaux -- Aspect politique -- Russie; Authoritarianism; Internet -- Political aspects; Social media -- Political aspects; Middle East; Russia (Federation); Soviet Union -- Former Soviet republics